2012
DOI: 10.1016/j.taap.2012.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Lipid raft: A floating island of death or survival

Abstract: Lipid rafts are microdomains of the plasma membrane enriched in cholesterol and sphingolipids, and play an important role in the initiation of many pharmacological agent-induced signaling pathways and toxicological effects. The structure of lipid rafts is dynamic, resulting in an ever-changing content of both lipids and proteins. Cholesterol, as a major component of lipid rafts, is critical for the formation and configuration of lipid rafts microdomains, which provide signaling platforms capable of activating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(158 citation statements)
references
References 85 publications
9
140
0
9
Order By: Relevance
“…In many types of cancer cells, including prostate, oncogenic receptors involved in aberrant signaling are concentrated in these lipid rafts (26,27). Lipid raft disruption affects homeostasis by altering cellular survival and apoptotic pathways (28). A recently published paper (29) demonstrated that g-T3 selectively accumulates within the lipid rafts and interferes with receptor tyrosine kinase dimerization.…”
Section: Resultsmentioning
confidence: 99%
“…In many types of cancer cells, including prostate, oncogenic receptors involved in aberrant signaling are concentrated in these lipid rafts (26,27). Lipid raft disruption affects homeostasis by altering cellular survival and apoptotic pathways (28). A recently published paper (29) demonstrated that g-T3 selectively accumulates within the lipid rafts and interferes with receptor tyrosine kinase dimerization.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid rafts have been shown to play important roles in cell responses to multiple extracellular stimuli, including cell-cell contact, cytokine and chemokine stimulation, drug therapy, and Abbinding reactions (32,33,44,45). For example, anti-CD95 (55,56) and anti-phospholipid Abs (57) mediate protein clustering in the plasma membrane followed by lipid raft formation.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid raft formation has been observed in response to multiple stimuli (31)(32)(33)(43)(44)(45). Generally, lipid rafts play an important role in the activation of signal transduction after extracellular stimulation.…”
Section: Anti-denv Ns1 Treatment Induces Ceramide Generationmentioning
confidence: 99%
“…Indeed, the different physical states of these phospholipids could drive specificity of peptide binding such as previously observed for different proteins [205,327]. The specific binding of a peptide to a saturated phospholipid could also suggest that this peptide is located in rafts since these structures contain a large percentage of this type of fatty acyl chain (for a review, see [329][330][331][332]). One should also be careful when using polyunsaturated phospholipids because they are very sensitive to oxidation [328].…”
Section: Determination Of the Maximum Insertion Pressure And Synergy mentioning
confidence: 90%